Strategic sports event management - Masterman, Guy (Routledge, 2014)
"The hosting of sports events whether large international events, or smaller niche events can have a significant and long lasting impact on the local environment, economy and society. Strategic Sports Event Management provides students and event managers with an insight into the strategic management of sports events of all scales and types, from international mega-events to school sports. Combining a unique conceptual framework with a practical, step by step guide to planning, organising, managing and evaluating events, the book explains the importance of adopting a strategic approach, showing how to implement strategies that lead to successful outcomes over the short and long-term. This fully revised and updated third edition uses international case studies in every chapter, from the NBA and NFL to Formula One and the English Premier League, offering real-world insight into both larger and smaller events. In addition, woven throughout the book are a series of in-depth studies of the London Olympic Games, the ultimate sporting event and an important point of reference for all practising and aspiring event managers.The book covers every key aspect of the sports event management process, includingsports organizations, such as the IOC, FIFA and IAAF, and their interactions with event partners, the media and promotersshort-term and long term benefits of the planning processevent impact and legacy operational functions including finance, ticketing, transport, venues, IT, human resources, and securitymarketing and communications, including social networking and new mediathe bidding process research and evaluation.Strategic Sports Event Management is the leading sports event management textbook and is now accompanied by a companion website containing a range of additional teaching and learning features. The book is important reading for all students of sport management or event management, and all practising event managers looking to develop their professional skills"-- Provided by publisher.